A Case Report of Sweet's Syndrome with Panuveitis and Rhegmatogenous Retinal Detachment. (17th November 2021) - Wang, Wenjuan; Wang, Xin; Zhao, Hongran; Cui, Yan
ABSTRACT: Purpose : To report a case of a patient who suffered from Sweet's syndrome with panuveitis in both eyes. Materials & Methods : Retrospective interventional case report. Results : A 54-year-old Chinese male patient complained of fever, painful skin lesions and blurry vision in both eyes lasting for 4 days. His visual acuity was hand motion in both eyes. Slit-lamp examination showed the hypopyon and severe vitreous opacification in both eyes. A skin pathology from head skin lesion demonstrated diffuse neutrophilic infiltration in the dermis with karyorrhexis. Based on the inspection above, the patient was diagnosed with Sweet's syndrome and given systemic corticosteroids therapy. However, he developed secondary rhegmatogenous retinal detachment in the right eye during his treatment. Conclusion : The association of bilateral uveitis with Sweet's syndrome has been described in this report.